2010
DOI: 10.1002/dneu.20792
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated neuritogenesis and maturation of primary spinal motor neurons in response to nanofibers

Abstract: Neuritogenesis, neuronal polarity formation, and maturation of axons and dendrites are strongly influenced by both biochemical and topographical extracellular components. The aim of this study was to elucidate the effects of polylactic acid (PLLA) electrospun fiber topography on primary motor neuron development, since regeneration of motor axons is extremely limited in the central nervous system and could potentially benefit from the implementation of a synthetic scaffold to encourage re-growth. In this analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
76
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 55 publications
6
76
0
Order By: Relevance
“…We typically obtain MN purity of >90% neurons 7,8 with this protocol and we have maintained DRG cultures for as long as one week without any significant fibroblast growth. Figure 2 shows typical MN appearance on glass and fibers after 24 hrs of culture and immunostaining.…”
Section: Representative Resultsmentioning
confidence: 99%
“…We typically obtain MN purity of >90% neurons 7,8 with this protocol and we have maintained DRG cultures for as long as one week without any significant fibroblast growth. Figure 2 shows typical MN appearance on glass and fibers after 24 hrs of culture and immunostaining.…”
Section: Representative Resultsmentioning
confidence: 99%
“…In other studies, aligned PLLA nanofibrous scaffold also supported the growth and extension of dorsal root ganglion (DRGs) [20,21] and primary motor neurons [20]. Primary motor neurons developed neurites earlier on PLLA nanofibers when compared to PLLA films [22]. However, no differences in neurite number and length were detected between aligned and random PLLA fibers [22].…”
Section: Effect Of Fiber Orientation and Sizementioning
confidence: 92%
“…Primary motor neurons developed neurites earlier on PLLA nanofibers when compared to PLLA films [22]. However, no differences in neurite number and length were detected between aligned and random PLLA fibers [22]. For human Schwann cells on PCL scaffolds, aligned fibers promoted cytoskeleton and nuclei alignment along the fiber.…”
Section: Effect Of Fiber Orientation and Sizementioning
confidence: 93%
“…Gertz et al showed that electrospun submicron fibers can significantly enhance neuritogenesis, maturation and the polarity formation of neurons compared to the two dimensional substrates, such as glass [12]. On the other hand, natural bio-polymers such as gelatin, which is produced by hydrolyzing collagen, should be more relevant than synthetic polymers in terms of biocompatibility [13].…”
Section: Introductionmentioning
confidence: 99%